Contaminants in Agriculture and Environment: Health Risks and Remediation 2019
DOI: 10.26832/aesa-2019-cae-0161-04
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals accumulation in crop plants: Sources, response mechanisms, stress tolerance and their effects

Abstract: Heavy metals are one of the major substances concerned with agricultural pollution. The heavy Chapter contents Introduction …………………………………………………………………………………………………….. Role and impacts of heavy metals in plants ……………………………………………………………….... Mechanism of heavy metals chelation in plants ……………………………………………………………. Response of plants towards different heavy metals ………………………………………………………... Silver (Ag) …………………………………………………………………………………………………… Aluminum (Al) ……………………………………………………………………………………………… Cadmium (Cd) ……………………………………………… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 52 publications
2
15
0
2
Order By: Relevance
“…The As content in the seeds and leaves of Parkia biglobosa does not show many discrepancies; this may be because of enzyme activities on this metal in these organs, degrading the metal to the minimum level of less toxic over time. This is in line with Kumar et al (2019) study, who have reported the plantʼs ability to metabolise heavy metals during nutrient acquisition. The following nutrient elements do not show any significant difference (p > 0.05); Mg, Na, K, P and N in seeds of Parkia biglobosa.…”
Section: Discussionsupporting
confidence: 92%
“…The As content in the seeds and leaves of Parkia biglobosa does not show many discrepancies; this may be because of enzyme activities on this metal in these organs, degrading the metal to the minimum level of less toxic over time. This is in line with Kumar et al (2019) study, who have reported the plantʼs ability to metabolise heavy metals during nutrient acquisition. The following nutrient elements do not show any significant difference (p > 0.05); Mg, Na, K, P and N in seeds of Parkia biglobosa.…”
Section: Discussionsupporting
confidence: 92%
“…Concepts of forest constructed wetlands are naturally for wastewater treatment systems, which are designed to utilize the natural purification processes involving wetland plants, substrates, and the associated microbes (Cheng et al, 2018;Hlihor et al, 2017). Bangkal tree and galam tree can adsorb higher Fe and Mn in condition pH <4 and lonkida tree and kayuputih higher to adsorb Fe and Mn in pH >4 (Kumar et al, 2019).…”
Section: Tree Species Selected For Swampy Forest Systemmentioning
confidence: 99%
“…The most common species in rhizosphere belong to genera Methylophilus, Methylovorus, Methylobacterium sp., Methylobacterium soli, Methylobacterium goesingense, Methylobacterium variabile, Methylobacterium suomiense, Methylopila helvetica, Methylobacterium thiocyanatum, Methylopilacapsulata and Methylobacterium aminovorans [1,17]. From soil samples, M. aminovorans TH-1, M. goesingense iEII3, M. soli YIM 48816T, M. suomiense, F20T, M. thiocyanatum, M. variabile GR3T, M. capsulata IM1T, and M. helvetica VKMB-189 are also recovered [16].…”
Section: 2 | Rhizospherementioning
confidence: 99%
“…PPFMs are highly abundant in both soil and phyllosphere region of plants and certain species dominate leaf surfaces are well identified (Table 1). To date trait methylotrophy is reported to span in seven families encompassing 15 genera (Figure 2) [17]. They improve both plant performance and also show plant protective characteristics.…”
Section: Introductionmentioning
confidence: 99%